2014
DOI: 10.1149/2.091404jes
|View full text |Cite
|
Sign up to set email alerts
|

TiO2Nanotube Films Prepared by Anodization in Glycerol Solutions for Photocathodic Protection of Stainless Steel

Abstract: TiO 2 nanotube array films were prepared on titanium foils by anodic oxidation in aqueous glycerol solutions with NH 4 F. The morphologies and properties of the films prepared in the solutions with different water contents were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), and UV-vis spectroscopy. The photocathodic protection effect of the films were evaluated by measuring the time evolution of the potential of 403 stainless steel coupled to the film photoanodes. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…HCOOH or Na 2 SO 4 is often used as a hole scavenger to capture the photogenerated holes and consequently enhance the charge separation of the photogenerated carriers in TiO 2 films [4,19,31,33]. In the photoelectrochemical measurement system for photocathodic protection, HCOOH and Na 2 SO 4 existed in the photoelectrochemical cell (photoanode cell), not in the corrosion cell with stainless steel.…”
Section: Photoluminescence and Photoelectrochemical Measurementsmentioning
confidence: 99%
“…HCOOH or Na 2 SO 4 is often used as a hole scavenger to capture the photogenerated holes and consequently enhance the charge separation of the photogenerated carriers in TiO 2 films [4,19,31,33]. In the photoelectrochemical measurement system for photocathodic protection, HCOOH and Na 2 SO 4 existed in the photoelectrochemical cell (photoanode cell), not in the corrosion cell with stainless steel.…”
Section: Photoluminescence and Photoelectrochemical Measurementsmentioning
confidence: 99%
“…Furthermore, Since Japanese scientists Fujishima and Honda first used semiconductor TiO 2 to decompose water into hydrogen and oxygen in 1972 [15], the photocatalytic material technology using semiconductor as photocatalyst has become one of hot research directions in the field of clean energy. As we know, great effort has been devoted by researchers around the world to the photoelectric catalysis of semiconductor TiO 2 under simulated sunlight, which is widely used in photocatalyst, sensors, biomedicine and other fields [16][17][18][19][20][21][22][23][24][25][26]. The main challenge is still the low photoelectrical conversion efficiency and stability of photocatalytic materials [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more researches were carried out on the photocathodic protection activity of some optoelectronic semiconductors, such as TiO 2 [1][2][3][4], ZnO [5,6], SnO 2 [7] and α-Fe 2 O 3 /Fe 3 O 4 [8]. Among them, TiO 2 -base materials were mostly studied for its high photosensitivity, low cost, low toxicity, and good chemical and thermal stability since Yuan and Tsujikawa [9] found that Cu could be protected from corrosion by adding TiO 2 coating under illumination.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the wide band gap of TiO 2 (anatase 3.2 eV, rutile 3.0 eV), the low energy utilization and rapid recombination of photogenerated electrons and holes reduced the photocathodic protection effect of these films. To address these drawbacks, highly ordered TiO 2 nanotube films possessing superior charge transport properties were prepared by electrochemical anodization method [1,10,11] and a variety of strategies have been developed to improve the light absorption of TiO 2 , such as decorating with narrow band gap semiconductors (ZnSe, CdSe, CdS) [12][13][14][15], metals (Au, Co, Ag, Fe) [16][17][18][19], non-metals (graphene, N, Si) [20][21][22], dye-sensitization (bacteriochlorophyll-C, phthalocyanine, porphyrin) [23][24][25] and doping with polymer conductors (polyaniline, pyrrole) [26][27][28].…”
Section: Introductionmentioning
confidence: 99%